The Effect of Organic Fertilizer from Coconut Flour Factory Waste on the Growth of Pakcoy (Brassica chinensis L.) Plants Experiencing Water Stress - Kawuwung, Stenly; Wurarah, Masje; Gedoan, Sumarayu P (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The availability of coconut raw materials in North Sulawesi has made the coconut flour industry increasingly developed. Waste water produced from the coconut flour manufacturing process is not utilized. Pakcoy (Brassica chinensis L.) is a vegetable that is widely cultivated because demand continues to increase due to public awareness of its nutritional value. The aim of the research is to analyze the effect of coconut flour factory waste as organic fertilizer, analyze the effect of water stress on pak choy plants, and analyze the effect of organic fertilizer from coconut flour factory waste on pak choy plants that experience water stress. The sample used was coconut flour factory waste in the form of coconut water from the PT coconut flour factory. Royal Coconut Airmadidi (Poleko). 25 liters of coconut water was fermented with 25 ml of EM4 for 10 days. This research used a Completely Randomized Design (CRD) consisting of 2 factors, 9 treatments and 5 replications. The research results showed that giving coconut water as an organic fertilizer had no significant effect on plant height, number of leaves and fresh weight of the plant. Water stress treatment of pak choy had a significant effect on the number of leaves and fresh weight of the plant, but had no significant effect on plant height.